Early Childhood Inclusive Education: The Role and Practice of Educational Institutions - Kalinina, Tetiana; Karnaukhova, Antonina; Mashovets, Marina; Shvaliuk, Tetiana; Telna, Olha (My University, 2021)
An important direction of society’s development is to ensure equal access of all children to education, including children with special needs. The practice of introducing inclusive education in early childhood educational institutions is a component of the practical implementation and protection of children’s rights and freedoms, regardless of any circumstances, including the state of health of the child. The purpose of the academic paper is to study the inclusive education and practice of preschool educational institutions for children with special educational needs in Ukraine and some European Union (EU) member states that joined EU in 2004-2017. The following methods have been used to study the practical aspects of inclusive education in preschool institutions in Ukraine and some EU countries, namely: analysis of the legal framework; method of comparative analysis; synthesis and analysis of quantitative indicators; questionnaires; systematization and generalization of statistical data. Results: Positive trends in the development and implementation of inclusive education in Ukraine have been identified, namely: the number of preschool educational institutions with inclusive groups has significantly increased, there has been a significant increase in the number of inclusive groups and children with special needs who study in groups with other children. The coverage of children with preschool educational institutions in Ukraine is only 58%, and children with special educational needs attend 28% of preschool educational institutions. At the same time, conditions for their training are created in only 25% of institutions, and the level of provision of teachers with special knowledge and skills of inclusive education is insufficient. A comparative analysis of the experience of the countries that joined EU in 2004-2017 suggests that membership in
Early Childhood Inclusive Education: The Role and Practice of Educational Institutions / T. S. Kalinina, A. V. Karnaukhova, M. A. Mashovets, T. M. Shvaliuk, O. A. Telna // Geintec : Gestão, Inovação e Tecnologias, 2021. – Vol. 11. – N. 3. – P. 911–929.
Keywords: спеціальні знання та вміння, особливі освітні потреби, учні дошкільного віку, захист прав, практичні аспекти; special knowledge and skills, special educational needs, preschool pupils, protection of rights, practical aspects